Neuroactive molecules and growth factors modulate cytoskeletal protein expression during astroglial cell proliferation and differentiation in culture. Issue 1 (15th October 2015) - Bramanti, Vincenzo; Grasso, Sonia; Tibullo, Daniele; Giallongo, Cesarina; Pappa, Rita; Brundo, Maria Violetta; Tomassoni, Daniele; Viola, Maria; Amenta, Francesco; Avola, Roberto
Abstract : Steroid hormones and neurotrophic factors regulate astroglial cell survival, proliferation, and differentiation in culture. The present study examines the interaction between glucocorticoids and growth factors (GFs) on cytoskeletal proteins and extracellular signal‐regulated kinase 2 (ERK2) expression in stressed astroglial cultures at 25 days in vitro, according to the following experimental condition. Pretreatment with basic fibroblast growth factor alone or in combination with dexamethasone 10 –9 M for 48 hr induced an enhancement of glial fibrillary acidic protein, vimetin, and ERK2 expression. Treatment with "progression" GFs alone and in the last 12 hr significantly increased the above‐mentioned markers' expression. The present study shows that glucocorticoids may cooperate with GFs or may abrogate their effects, depending on the experimental culture conditions used as well as the exposure time and the types of GFs added. Our findings provide evidence of interactive dialogue between GFs and neurosteroids in cultured astrocytes. This may have implications in the therapeutic approach to neurologic disorders associated with astrogliosis. © 2015 Wiley Periodicals, Inc. Abstract : This study provides evidence of the intertwined dialogue between neuroactive molecules such as dexamethasone and both "competence" and "progression" growth factors in regulating astrocyte cytoskeletal proteins and ERK2 expression during astroglial cell proliferation and differentiation processes.